The social dynamics involved in recovery and return to sport following a sport-related concussion: A study of three athlete-teammate-coach triads. (January 2021) - Caron, Jeffrey G.; Benson, Alex J.; Steins, Rebecca; McKenzie, Laura; Bruner, Mark W.
Abstract: An athlete's connection to their team and team members is an important part of their sport experience. However, researchers currently know little about the nature of these social dynamics with respect to concussed athletes. Our study explored athletes' recovery and reintegration into the team environment following a sport-related concussion. We conducted semi-structured interviews with each member of three athlete-teammate-coach triads ( N = 9 ). We analysed the data using thematic narrative analysis and present the results as three stories that focused on each athlete's experience. For Cassie, we found two major plot points in her story: the transition in her role (and shift in identity) from athlete to student assistant coach/team manager and, once recovered, back to an athlete on the team. For Jess, we found that the main plot in her story was "pressure". Specifically, the interplay between internal (placed on herself) and external (perceived from teammates and coaches) pressures to return to sport. In the third and final story, the main plot point was the tensions that arose from Jaden's preferences for social support and the type of support that his teammates and coaches believed he needed during his recovery. Our results highlight the interplay between athlete's personal and social identities, feelings of pressure to return and readiness, and the challenges of providing the right amount and type of social support. This research contributes to our limited understanding of the social dynamics involved in athletes' return to sport following a concussion. Highlights: We studied the social dynamics of returning to sport following concussion. Three athlete-teammate-coach triads participated in semi-structured interviews. Cassie's story centered around the concept of identity, which shifted with her changing roles. Pressures placed on oneself and perceived from others characterized Jess's story. Jaden's story revolved around the type of support he wanted versus what he believed he received.